Primary CNS lymphoma. Issue 6 (November 2015) - Touitou, Valerie; LeHoang, Phuc; Bodaghi, Bahram
Abstract : Purpose of review: Despite recent progress, the diagnosis of primary CNS lymphoma (PCNSL) remains a challenge and is often delayed by several months. Treatment options are still debated and the prognosis of PCNSL lymphoma is poor for most patients. This review will describe recent progress and future orientations for diagnosis of PCNSL and report on the recent trends regarding therapeutic options. Recent findings: PCNSL must be suspected in cases of chronic posterior uveitis, especially in patients over 50 years old. Diagnosis is based on cytology and molecular analysis of clonality of vitreous samples. Intraocular interleukin (IL)-10 level has proved to be a valuable tool for screening purposes in cases where there is a suspicion of primary vitreoretinal lymphoma. Intraocular cytokine dosage could also be a useful marker to follow the therapeutic response of patients with PCNSL. Treatment of PCNSL remains under debate. Summary: Diagnosis of PCNSL is challenging. Suspicion relies on clinical history and on IL-10 and IL-6 levels in ocular fluid samples. Definite diagnosis is based on cytology and molecular analysis of clonality. New diagnostic and prognostic markers are currently evaluated. Whether isolated vitreoretinal lymphoma should be treated locally or with systemic treatment remains highly controversial.